2007
DOI: 10.1007/s00467-007-0595-y
|View full text |Cite
|
Sign up to set email alerts
|

NPHS2 (podicin) mutations in Turkish children with idiopathic nephrotic syndrome

Abstract: The podocin (NPHS2) gene encodes podocin protein, which has an important role in glomerular ultrafiltration and controlling slit membrane permeability. The detection of an NPHS2 mutation affects the treatment plan for children with nephritic syndrome (NS). The frequency and spectrum of podocin mutations in the Turkish population have remained largely unknown. The aim of this study was to screen for podocin mutations in Turkish patients with steroid-resistant NS (SRNS) and to compare it with other published ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 38 publications
4
49
3
1
Order By: Relevance
“…More specifically, in five patients, we observed different variants in the NPHS2 gene (two homozygous and three compound heterozygous) that were already described as potentially pathogenic. [16][17][18][19][20] In patient 1, we observed the non-neutral polymorphic variant -52 C.G, which was previously reported to reduce NPHS2 transcription by abolishing the binding of the regulatory factor upstream transcription factor 1 (USF1) to the NPHS2 promoter. 16 This patient was homozygous, having inherited the two variants from each of two nonaffected parents, and displayed a significantly reduced podocin expression at the biopsy (Supplemental Figure 1), even if he was affected by a minimal change disease, where levels of podocin are usually normal.…”
Section: Resultsmentioning
confidence: 91%
“…More specifically, in five patients, we observed different variants in the NPHS2 gene (two homozygous and three compound heterozygous) that were already described as potentially pathogenic. [16][17][18][19][20] In patient 1, we observed the non-neutral polymorphic variant -52 C.G, which was previously reported to reduce NPHS2 transcription by abolishing the binding of the regulatory factor upstream transcription factor 1 (USF1) to the NPHS2 promoter. 16 This patient was homozygous, having inherited the two variants from each of two nonaffected parents, and displayed a significantly reduced podocin expression at the biopsy (Supplemental Figure 1), even if he was affected by a minimal change disease, where levels of podocin are usually normal.…”
Section: Resultsmentioning
confidence: 91%
“…Mutations of this proline residue are known causes of protein dysfunction throughout species. A P134S mutation in MEC-2 (MEC-2 P134S ) causes touch insensitivity in the nematode (22), and the equivalent P118L mutation in humans causes SRNS (3,4,20,21). Because it has been shown that a mutation of this conserved proline in stomatin (P47S) changes the membrane topology of stomatin (31), we concentrated on the molecular mechanisms that cause SRNS in patients bearing the podocin mutation P118L (corresponding to P120L in the mouse protein, collectively named podocin P3 L hereafter).…”
Section: Podocinmentioning
confidence: 99%
“…[Arg229Gln];[mut] that causes SRNS with a median age at diagnosis of 13 years (range, 0-39 years) and progression to ESRD by 26 years (range, 10-50 years) 7,[13][14][15][16][17][18] . Nevertheless, the p.Arg229Gln variant in the homozygous state does not cause SRNS 19,20 .…”
Section: Introductory Paragraphmentioning
confidence: 99%
“…[Arg229Gln]; [mut] in 318 families from French and other SRNS cohorts [13][14][15][16][17][18] and found a striking difference (P = 1.2 × 10−35; Table 1). Notably, whereas mutations in the last two exons (7 and 8) were rare in cases with [ Out of the 56 mutations located in exons 1-6, only 4 were associated with p.Arg229Gln in cases with SRNS, and these accounted for only 8 of 71 (11%) total p.Arg229Gln-associated alleles (Tables 1 and 2) Table 2).…”
mentioning
confidence: 99%